2016
DOI: 10.1007/s13197-016-2286-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of seed oils from different grape cultivars grown in China

Abstract: To explore the potential of the large amount of grape pomace in wineries of China, oils of three Eurasian grape cultivars (Chardonnay, Merlot and Carbernet Sauvignon) and two Chinese traditional grape cultivars (Vitis amurensis and Vitis davidii), were characterised. The results showed seed oil properties differ for various grape varities. Grape seed oils were demonstrated to be good sources of polyunsaturated fatty acid (PUFA) (63.88-77.12 %), sterols (227.99-338.83 mg/100 g oil) and tocotrienols (320.08-679.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 26 publications
9
44
2
1
Order By: Relevance
“…Razagui and Merlot seed oils represented the lowest total phenol contents with 58.18 and 56.36 mg GAE/kg oil, respectively, as compared with the other varieties. These results were in accordance with the total phenol contents of Australian grape seed oils (59.0–115.5 mg GAE/kg oil) obtained by Bail, Stuebiger, Krist, Unterweger, and Buchbauer () and higher than those of Chinese grape seed oils (46.60–98.19 mg GAE/kg oil) reported by Wen et al (). In Turkey, the total phenol contents of grape seed oils ranged from 21.90 to 47 mg GAE/kg (Gulcin, Buyukokuroglu, Oktay, & Kufrevioglu, ), while they ranged from 10.68 to 34.43 mg GAE/kg oil in Spain (Garavaglia, Markoski, Oliveira, & Marcadenti, ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Razagui and Merlot seed oils represented the lowest total phenol contents with 58.18 and 56.36 mg GAE/kg oil, respectively, as compared with the other varieties. These results were in accordance with the total phenol contents of Australian grape seed oils (59.0–115.5 mg GAE/kg oil) obtained by Bail, Stuebiger, Krist, Unterweger, and Buchbauer () and higher than those of Chinese grape seed oils (46.60–98.19 mg GAE/kg oil) reported by Wen et al (). In Turkey, the total phenol contents of grape seed oils ranged from 21.90 to 47 mg GAE/kg (Gulcin, Buyukokuroglu, Oktay, & Kufrevioglu, ), while they ranged from 10.68 to 34.43 mg GAE/kg oil in Spain (Garavaglia, Markoski, Oliveira, & Marcadenti, ).…”
Section: Resultssupporting
confidence: 91%
“…Carignan and Syrah had the highest total tocopherol contents with 181.35 and 125.35 mg/kg oil, respectively, while Sangiovese and Razaki had the lowest ones with 22.91 and 13.89 mg/kg oil, respectively. Similar results were obtained by Wen et al () in the case of Chinese grape seed oils (62−175.87 mg/kg oil). Göktürk Baydar, Özkan, and Sema Çetin () found that total tocopherol contents of Turkish grape seed oils ranged from 143.05 to 358.75 mg/kg oil.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Wen et al compared the composition of five GSO varieties in China (Chardonnay, Merlot, Cabernet Sauvignon , Vitis amurensis , and Vitis davidii ) and found that GSO from Cabernet Sauvignon contained the highest concentrations of squalene, total sterols, total tocopherols, and total phenolics among them. This study investigated the effects of Cabernet Sauvignon GSO on hyperlipidemia, inflammation, and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%